The paradox of creativity education - Altabaa, Homam (2020)
This work is a literature-informed conceptual study that examines the dynamics of creativity teaching and learning. It aims to explore the major topics of creativity education and to identify the major challenges facing lecturers and students in this field. The methodology of the study comprises a comprehensive review of the research on creativity education, individual interviews with experts in teaching creativity, and focus group interviews with students who have studied creativity as a university course. The findings of the study center first upon foundational issues of defining creativity from an Islamic perspective and upon the teachability of creativity at the university level. Additionally, the study examines topics such as class environment, academic challenges, student attitude, personality and motivation in relation to teaching creativity.